PENINGKATAN MOTIVASI DAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN MEDIA GAMBAR DI SEKOLAH DASAR - Yonarlianto Tembang; Sulton Sulton; Suharjo Suharjo (Graduate School of Universitas Negeri Malang, 2017)
This study aims to determine the improvement of motivation and student learning outcomes during the implementation of learning using learning model think pair share assisted images media. The subject were students of the fourth grade at Sd Inpers Mangga Dua Merauke. The analysis technique used descriptive analysis. Data collections teqniques used: observation, questionnaires, and tests. The result of this study showed that the implementation of learning model think pair share and images media was effective to improve motivation and learning outcomes. The implementation of learning model think pair share and images media can improve average score of learning motivation from 74.91% in cycles 1 into 87.27% in cycles 2. The improvement of student learning outcome was 68,81% in cycle 1 and 86.36% in cycles. The results indicate that implementation learning model of think pair share and images media can improve motivation and learning outcomes.Penelitian ini bertujuan untuk mengetahui peningkatan motivasi dan hasil belajar siswa dengan menggunakan model pembelajaran think pair share berbantuan media gambar. Subjek penelitian ini adalah siswa kelas IV SD Inpres Mangga Dua Merauke. Teknik analisis menggunakan analisis deskriptif. Pengumpulan data menggunakan observasi, angket, dan tes. Hasil penelitian ini terdapat peningkatan motivasi belajar siswa rata-rata 74,91% pada siklus I menjadi 87,27% pada siklus 2. Peningkatan hasil belajar kognitif siswa meningkat pada siklus I sebesar 68,81% pada siklus II mencapai 86,36%. Dengan demikian, hasil ini menunjukkan bahwa melalui model pembelajaran think pair share berbantuan media gambar dapat meningkatkan motivasi dan hasil belajar siswa.